POTENSI ANALOGI MATEMATIS DIKAJI DARI GAYA KOGNITIF SISWA DALAM MATERI BENTUK AKAR DI SEKOLAH MENENGAH PERTAMA - Kusumawati, Evi; Sugiatno, Sugiatno; Nursangaj, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract                                                                            This study aimed to explain the potential of mathematical analogy studied from the cognitive style of students in the subject of radical form of class VIII F SMP Negeri 1 Sungai Raya. The research method was descriptive method with case study research. The subjects of this study were 5 students of class VIII F SMP Negeri 1 Sungai Raya 2016/2017 consisted of 1 Independent cognitive field students and 4 students of cognitive field dependent. The results of this study showed that: (1) The potential of mathematical analogy of cognitive style students of Field Independent has a high potential with a percentage of 83.33%; (2) The Potential of mathematical analogy of cognitive style students of Field Dependent has varying potential; 2 students have a high mathematical analogy potential with a percentage of 83.33%; 1 student has the potential of a moderate mathematical analogy with a percentage of 75%; and 1 student has the potential of a mathematical analogy that is very low with a percentage of 41.67%. Keywords: Potential of Mathematical Analogy, Cognitive Style